Transformation of Gothic to Neo-Gothic Architecture in St. Joseph Gedangan Church Building, Semarang - Nuraini, Aisyah; Indarti, Fitri Dwi (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2024)
One of the architectural styles that underwent significant evolution was the Gothic style, which later developed into Neo-Gothic or Gothic Revival. These changes are influenced not only by aesthetic factors but also by social, technological, and political advances in various periods. The Neo-Gothic architectural style emerged in the late 18th to early 20th centuries as a revival of Gothic architecture from the medieval era. St. Joseph Gedangan Catholic Church in Semarang is one of the historical buildings registered as a cultural heritage, which carries a Neo-Gothic architectural style with a little Gothic touch. This study uses a qualitative method based on case studies to examine the transformation of architectural styles in St. Joseph Church Gedangan Semarang. This church adopts the Neo-Gothic style, which results from a transformation of the Gothic style that developed in Indonesia. This process of change illustrates how European architectural styles can be adapted to local conditions in Indonesia. St. Joseph Gedangan Church retains the typical elements of Gothic architecture but is adapted to the climate of Semarang City. The materials are available, and the size of the building is more proportional compared to traditional Gothic buildings. This change reflects the advancement of technology as well as the functional needs of church buildings in Indonesia that combine the beauty of classical architecture with modern efficiency.